2011
DOI: 10.1002/lapl.201110093
|View full text |Cite
|
Sign up to set email alerts
|

CVD-diamond external cavity nanosecond Raman laser operating at 1.63 µm pumped by 1.34 µm Nd:YAP laser

Abstract: The external cavity CVD-diamond Raman laser generating at the wavelength of 1.63 µm was demonstrated for the first time. The laser was pumped by the Q-switched 1.34 µm Nd:YAP laser. Raman laser output energy of 47 µJ in the 6 ns long pulse with the fundamental spatial beam profile was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
0
17
2
Order By: Relevance
“…23,24 However, because our observed lasing peaks were different from the typical reported Raman peaks (1333 cm À1 and 1600 cm…”
contrasting
confidence: 91%
“…23,24 However, because our observed lasing peaks were different from the typical reported Raman peaks (1333 cm À1 and 1600 cm…”
contrasting
confidence: 91%
“…As high as 1.21 W of average output power at 1666 nm is achieved at a pump power of 20.3 W and at a pulse repetition frequency (PRF) of 5 kHz. The pulse width is as short as 27 ns, and the pulse energy is 242 μJ, which is about four times bigger than the mentioned results achieved by Jelínek et al (47 μJ) [6], corresponding to a peak power of 8.96 kW. To our knowledge, this is also the highest Raman output peak power around 1.6 μm.…”
mentioning
confidence: 52%
“…To our knowledge, only Jelínek et al have demonstrated a chemical vapor deposited (CVD)-diamond Raman laser operating at 1.63 μm; in their demonstration, a flashmap-pumped passively Q-switched Nd:YAP laser operating at 1.34 μm with V 3 :YAG as a saturable absorber was employed as the pump source. Raman laser output energy of 47 μJ with a pulse width of 6 ns was obtained [6].The most commonly used Raman active media include YVO 4 [7,8], PbWO 4 [9], KGdWO 4 2 [10], SrWO 4 [11], and BaWO 4 [ [12][13][14][15]. BaWO 4 is regarded as an excellent Raman active crystal suitable for a wide range of pumped pulse durations from picoseconds to nanoseconds for its advantages of high Raman gain efficiency and excellent thermal and mechanical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Raman effect is widely used for frequency shift of laser radiation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. By using stimulated rotational Raman scattering (SRRS) of CO 2 laser radiation, coherent far infrared (FIR) radiation can be gener ated efficiently, which is necessary for laser photo chemistry, remote sensing and laser isotope separation of UF 6 [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%